Urban pests like cockroaches, mosquitoes, and flies can transmit human diseases that cause health problems in the society. Currently, mosquito is main insect that transmit very deadly diseases, such as dengue fever, cikungunya, and malaria. Prevention of those diseases is generally focused on controlling the vectors in various ways, such as fogging, the use home pesticides, sanitation, use of mosquito repellents, electric rackets, and other traditional ways developed by the community (mosquito - Titiek Siti Yuliani; Hermanu Triwidodo; Kooswardhono Mudikdjo; Nurmala K. Panjaitan; Sjafrida Manuwoto (Forum Pasca Sarjana, 2011)
Urban pests like cockroaches, mosquitoes, and flies can transmit human diseases that cause health problems in the society.  Currently, mosquito is main insect that transmit very deadly diseases, such as dengue fever, cikungunya, and malaria. Prevention of those diseases is generally focused on controlling the vectors in various ways, such as fogging, the use home pesticides, sanitation, use of mosquito repellents, electric rackets, and other traditional ways developed by the community (mosquito net, gauze, water).  The purpose of this study was to describe the relationship between characteristics of peoples live in Jakarta (based on age, sex, education, and income level) to their behavior in using home pesticides and to know the impact of those pesticides to peoples and pets live in their houses.  Research sites were purposively directed to the areas that were appropriate with the substances and purposes of this study.  Interviewed was conducted to the respondents (housewives) and inspection of their houses were also conducted to classify their houses as clean, moderately clean, and dirty or slum.  Based on a survey to 155 respondents, it was revealed that respondent characteristics as well as their house conditions influenced the behavior of those respondents in choosing home pesticides.  Majority of  housewives (28.21%) use liquid pesticides which were contains the active ingredient of cypermethrin 0.4 g/l, imiprotrin 0.32 g/l, and transflutrin 0.2 g/l.  In addition, 47.26% of them ignored the instruction written on the label in using those pesticides.  Awareness of those respondents was still low in terms of dumping the package of pesticides; 96.64% of respondents dumped pesticides to the dumpster near their houses.  Commercial advertencies from electronic media, especially TV, influence half of the respondents (52.74%) in choosing home pesticides used.  In general, it can be summarized that the awareness of respondents in using home pesticides were still low.  Most housewives did not know the danger of those chemicals and how to use it properly.  Only 38.46% of them used non-chemical methods, such as insect net.   Key words: home pesticides, active ingredient, urban pest, housewife, the environment